Advances in Experimental Medicine and Biology
DOI: 10.1007/978-0-387-74087-4_2
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Nutritional Regulation of Lipogenic Genes in the Ruminant Lactating Mammary Gland

Abstract: The effect of nutrition on milk fat yield and composition has largely been investigated in cows and goats, with some differences for fatty acid (FA) composition responses and marked species differences in milk fat yield response. Recently, the characterization of lipogenic genes in ruminant species allowed in vivo studies focused on the effect of nutrition on mammary expression of these genes, in cows (mainly fed milk fat-depressing diets) and goats (fed lipid-supplemented diets). These few studies demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
232
2
10

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(263 citation statements)
references
References 171 publications
(235 reference statements)
19
232
2
10
Order By: Relevance
“…Conversion of acetate to malonyl-CoA, catalyzed by ACC, is considered to be the ratelimiting step (Bauman and Davis, 1974). Recent studies have reported that expression of acyl-CoA synthetase short-chain family member ACSS2 gene increases in mammary tissue of cows during lactation, and that the changes in transcript Figure 4 Synthesis of milk fat in the bovine mammary epithelial cell (adapted from Bernard et al, 2008). Abbreviations: ACC, acetyl-CoA carboxylase; AGPAT, 1-acyl glycerol 3-phosphate acyl transferase; CD36, cluster of differentiation 36; CLD, cytoplasmic lipid droplet; CoA, coenzyme A; CM, chylomicron; DGAT, diacylglycerol acyltransferase 1; ER, endoplasmic reticulum; FA, fatty acid; FABP, fatty acid binding protein; FAS, fatty acid synthase; Glut 1, glucose transporter 1; GPAT, glycerol-3 phosphate acyl transferase; LPL, lipoprotein lipase; MFG, milk fat globule; SCD, stearoyl-CoA desaturase; TAG, triacylglyceride; VLDL, very low density-lipoprotein.…”
Section: Mammary Lipogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…Conversion of acetate to malonyl-CoA, catalyzed by ACC, is considered to be the ratelimiting step (Bauman and Davis, 1974). Recent studies have reported that expression of acyl-CoA synthetase short-chain family member ACSS2 gene increases in mammary tissue of cows during lactation, and that the changes in transcript Figure 4 Synthesis of milk fat in the bovine mammary epithelial cell (adapted from Bernard et al, 2008). Abbreviations: ACC, acetyl-CoA carboxylase; AGPAT, 1-acyl glycerol 3-phosphate acyl transferase; CD36, cluster of differentiation 36; CLD, cytoplasmic lipid droplet; CoA, coenzyme A; CM, chylomicron; DGAT, diacylglycerol acyltransferase 1; ER, endoplasmic reticulum; FA, fatty acid; FABP, fatty acid binding protein; FAS, fatty acid synthase; Glut 1, glucose transporter 1; GPAT, glycerol-3 phosphate acyl transferase; LPL, lipoprotein lipase; MFG, milk fat globule; SCD, stearoyl-CoA desaturase; TAG, triacylglyceride; VLDL, very low density-lipoprotein.…”
Section: Mammary Lipogenesismentioning
confidence: 99%
“…Studies in cows have revealed the occurrence of transcripts encoding for CD36 (Bionaz and Loor, 2008b) and several SLC27A isoforms (1, 2, 3, 5 and 6; Bionaz and Loor, 2008a) in mammary tissue and demonstrated that CD36 and SLC27A6 mRNA abundance increases during the first months of lactation (Bionaz and Loor, 2008b). Even though the mechanisms responsible for the transport of fatty acids across the capillary endothelium and interstitial space are not well characterized (Barber et al, 1997;Bernard et al, 2008), it has been suggested that SLC27A6, ACSL1 and FABP3 are involved in the coordinate regulation of channelling fatty acids towards milk fat TAG synthesis in the bovine mammary gland (Bionaz and Loor, 2008a).…”
Section: Mammary Lipogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…The t10,c12-CLA isomer has demonstrated inhibition on the gene expression of the stearoyl-CoA desaturase enzyme (Baumgard et al, 2002b) and, in vivo, the enzyme activity on the mammary gland can be estimated through the product/ substrate ratio of some fatty-acid pairs under its action (Bernard et al, 2008). The absence of effect on c9,t11-CLA/ t11-18:1 ratio index could be because of the presence of the c9,t11-CLA isomer in the CLA supplement.…”
mentioning
confidence: 99%